Termite mound clay as material for grain silo construction (2007)
Silos are the most appropriate structures for the bulk storage of grains. Their performances are greatly influenced by the materials of construction and the climatic environment where they are used. Under the warm and humid climate prevalent in Nigeria, metal silos which are the predominant structures used for grain storage experience moisture condensation, resulting in grain deterioration. There is therefore the need to source for construction materials that will eliminate moisture condensation, durable, easy to construct, cheap and readily available to farmers. Termite mound clay was identified as a potential material. A 5.6m3 silo was designed and the prototype constructed with treated termite mound clay bricks. Temperatures were measured inside and outside the silo and the quality of grain stored in the silo was monitored over a period of two months. Viability tests of stored grain were also undertaken. Minimum and maximum temperatures outside the silo were 21°C and 36°C as against 20°C and 30°C inside the silo. Temperature fluctuation within the silo was 9.5 °C compared with 10.3 °C outside. Grain quality was maintained during the storage period, the viability before and after storage were 88% and 84% respectively. The treated termite mound clay silo demonstrated great potential for reducing temperature fluctuations and maintaining grain quality in storage. It is recommended that the simulation of moisture content, relative humidity and temperature profiles under full load should be undertaken. A comparative evaluation of the silo performance with those of other materials of silos construction should also be undertaken.